2004
DOI: 10.4018/jgim.2004070102
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Internet Banking Adoption and Use Behavior

Abstract: This study investigates adoption/use behavior within the context of Hong Kong Internet Banking services. A research framework based on the extended Technology Acceptance Model (TAM2) and Social Cognitive Theory is developed to identify factors that would influence the adoption and continue use of Internet Banking. Structural Equation Modeling (SEM) is employed to examine the entire pattern of inter-correlations among the eight proposed constructs, and to test related propositions empirically. A survey involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(139 citation statements)
references
References 12 publications
(40 reference statements)
8
69
0
4
Order By: Relevance
“…Moreover, as subjective norm becomes more positive, behavioural intention to participation also becomes more positive (Kuo & Dai, 2012). Further, studies have shown no significant relationship between SN and intention (Chau & Hu, 2001;Lewis et al, 2003) whereas other studies depict the opposing outcome (Chan & Lu, 2004;Jen-Ruei et al, 2006;Ramayah et al, 2004;Taylor & Todd, 1995;Venkatesh & Davis, 2000). It is with these findings that this study states the subsequent hypothesis: Ajzen (1985) identified perceived control behaviour as influencing behavioural intention and directly influencing actual behaviour.…”
Section: H1supporting
confidence: 48%
“…Moreover, as subjective norm becomes more positive, behavioural intention to participation also becomes more positive (Kuo & Dai, 2012). Further, studies have shown no significant relationship between SN and intention (Chau & Hu, 2001;Lewis et al, 2003) whereas other studies depict the opposing outcome (Chan & Lu, 2004;Jen-Ruei et al, 2006;Ramayah et al, 2004;Taylor & Todd, 1995;Venkatesh & Davis, 2000). It is with these findings that this study states the subsequent hypothesis: Ajzen (1985) identified perceived control behaviour as influencing behavioural intention and directly influencing actual behaviour.…”
Section: H1supporting
confidence: 48%
“…Respondent A pointed out that the positive feedback of using BIM has actually improved the company image. The views of experts support the findings of Venkatesh & Davis (2000), and Chan & Lu (2004) that image of using an innovation affects a person's perceived usefulness.…”
Section: Image Of Using the Bim System And Perceived Usefulness Of Thsupporting
confidence: 63%
“…Social cognitive theory has been applied in the technology innovation literature to analyze the internal and external social environment that influences technology adoption [22]. Social cognitive theory which is also called as social learning theory states that individual behaviour is determined by their social environment [23].…”
Section: Technology Adoption Theoriesmentioning
confidence: 99%